Mom & me & mom - Angelou, Maya. (New York : Random House, 2013)
The celebrated author shares the intimate story of her relationship with her mother, relating the events that prompted her mother to send young Angela to Arkansas to live with her grandmother and the complicated fallout that shaped their family life.
Keywords: Angelou, Maya -- Family; Authors, American -- 20th century -- Biography; Entertainers -- United States -- Biography; African American authors -- Biography